Quantification of upper body strategy during gait in children with spastic diplegia using a summary parameter. Issue 15 (17th November 2020) - Cimolin, Veronica; Condoluci, Claudia; Manzia, Carlotta Maria; Girolamo, Gabriella di; Galli, Manuela
Abstract: A summary measure for quantification of the upper body position (Upper Body Profile Score [UBPS]) during gait was proposed and used in 38 children with Cerebral Palsy (CP) and 15 healthy children (Control Group: CG). Patients with CP exhibited higher values of most of the summary parameters of the upper body position than the CG. The higher influence on UBPS is by the upper body position in sagittal and transversal plane. A significant and fair correlation between UBPS and Gait Profile Score (a summary measure to quantify the lower limb gait pattern) suggests that altered upper body movements during walking could be associated with the presence of lower limb impairments.